2000
DOI: 10.1046/j.1439-0442.2000.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Restraint Stress on Regional Brain Neurotransmitter Levels in Stress‐Susceptible Pietrain Pigs

Abstract: Concentrations of noradrenaline (NA), adrenaline (A), dopamine (DA), 5-hydroxytryptamine (5-HT), the DA metabolites 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA) and the main 5-HT metabolite 5-hydroxyindole-3-acetic acid (5-HIAA) were measured using HPLC in 16 brain areas of control and immobilized Pietrain pigs. The animals were immobilized for 15, 30 and 60 min in the prone position. Control pigs showed patterns of regional distribution of brain monoamines similar to those described for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…In fish under acute stress, cortisol levels can easily increase more than tenfold, from 10-20 ng/ml to over 350 ng/ml (Wendelaar Bonga 1997). Both basal levels as well as increases in cortisol level during stress are in the same range as those in the mammalian stress response (Van Cauter et al 1996, Hennessy et al 1997, Piekarzewska et al 2000.…”
Section: Stress and The Immune Systemmentioning
confidence: 84%
“…In fish under acute stress, cortisol levels can easily increase more than tenfold, from 10-20 ng/ml to over 350 ng/ml (Wendelaar Bonga 1997). Both basal levels as well as increases in cortisol level during stress are in the same range as those in the mammalian stress response (Van Cauter et al 1996, Hennessy et al 1997, Piekarzewska et al 2000.…”
Section: Stress and The Immune Systemmentioning
confidence: 84%
“…Invasive neurobiological approaches based on functional neuroanatomy (sheep: da Costa et al 2004, Rivalland et al 2007, Vellucci & Parrott 1994, intracerebroventricular pharmacology (pigs: Johnson et al 1994, Salak-Johnson et al 2004, and neurochemical brain content (e.g. in pigs, Kanitz et al 2003, Loijens et al 2002, Piekarzewska et al 1999, Piekarzewska et al 2000, Zanella et al 1996 have demonstrated the involvement of neuropeptides such as CRF and enkephalins in different brain areas including the hypothalamus, brainstem and cortices. While neuroanatomical methods have been used to describe the immunoreactive content of brain areas (in sheep: Tillet 1995; in pigs: Kineman et al 1989, Leshin et al 1996, Niblock et al 2005, Rowniak et al 2008; in large mammals: Tillet & Kitahama, 1998), and neuronaltracing methods have been used to describe the interconnections between some of these brain areas (sheep: Qi et al 2008, Rivalland et al 2006, Tillet et al 1993pigs: Chaillou et al 2009), no dynamic functional information is available about the functional interactions among these different factors.…”
Section: Emotional Reactionmentioning
confidence: 99%
“…Ursinus et al [8] were the first to show a link between tail biting behavior and the serotonergic system, by showing a decrease of blood serotonin in both tail biting and victim pigs. Stressful situations change serotonin activity in the brain [22,23].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In pigs, the dopaminergic system has been related to exploratory propensity [26] and the frustration level during a delay test [27]. Dopamine responds to stressful situations [22,23], for example, it has been shown that stress caused by restraining pigs increases dopamine turnover in certain brain areas [23].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation